2010
DOI: 10.1002/14651858.cd007624.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation interventions for improving physical and psychosocial functioning after hip fracture in older people

Abstract: Some outcomes may be amenable to psychosocial treatments; however, there is insufficient evidence to recommend practice changes. Further research on interventions described in this review is required, including attention to timing, duration, setting and administering discipline(s), as well as treatment across care settings. To facilitate future evaluations, a core outcome set, including patient-reported outcomes such as quality of life and compliance, should be established for hip fracture trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 68 publications
1
56
0
2
Order By: Relevance
“…Focusing on optimal rehabilitation in order to improve patients' physical independence may increase the rate of patients remaining home-dwellings after a hip-fracture [26]. Results from the Trondheim Hip Fracture Trial showed that immediate admission before initial surgery to a ward delivering comprehensive geriatric care (CGC) improved mobility at four months as compared with the usual orthopaedic care (OC).…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on optimal rehabilitation in order to improve patients' physical independence may increase the rate of patients remaining home-dwellings after a hip-fracture [26]. Results from the Trondheim Hip Fracture Trial showed that immediate admission before initial surgery to a ward delivering comprehensive geriatric care (CGC) improved mobility at four months as compared with the usual orthopaedic care (OC).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first metaanalysis of extended rehabilitation for people with hip fractures, and the results support its effectiveness. Other reviews either have been very broad, preempting a concrete conclusion, or have had different scopes, [43][44][45][46] but none covered only extended rehabilitation. For instance, in their 2011 Cochrane review, Handoll et al 11 studied mobilization strategies across all care settings (inpatient acute care, inpatient rehabilitation, community-based rehabilitation), making the scope of the review very broad, which contributed heterogeneity to the effects and consequently made it difficult to compare the studies included in their review or to pool the estimates for outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…ESD is shown to reduce the burden on acute providers and support patient recovery. 65 The funding of ESD through joint commissioning between the acute NHS providers, GPs, social services and central government highlights the role of joint working and resource pooling, but there remain variations across the UK, especially in rural areas, where a lack of funding can limit provision. 66,67 Intermediate services provide transitional, 'step-down' care between acute hospital and the domestic environment (usually for 30 days).…”
Section: Hospital Discharge and Patient Safety: Reviews Of The Literamentioning
confidence: 99%
“…69 The recent Cochrane reviews of long-term rehabilitation in care homes show no evidence of negative health outcomes. 65,70 A similar initiative is the introduction of reablement services. These usually involve a dedicated package of social care to support daily living in the immediate period following discharge (e.g.…”
Section: Hospital Discharge and Patient Safety: Reviews Of The Literamentioning
confidence: 99%